Influence of MgO content on bio-ash slagging propensity and flowability under mild reducing environment. (15th August 2022) - Alam, Tanvir; Hoadley, Andrew; Zhang, Lian
Highlights: Slagging of bio-ash and flowability was examined in an inclined plate. Bio-slag flowability for 6–16 wt% of MgO is slow for a relatively high viscosity. 6–16 wt% of MgO exerted little influence on the ash fusion temperature. CaO is most influential in depolymerising ash matrix to promote its flowability. Co-presence of K2 O and Al2 O3 caused a significant decrease in the slag flowability. Abstract: In this work, an inclined plate technique was used to investigate the slagging propensity of bio-ashes and the flowability of the resulting bio-slags in a reducing gas environment at 1300 °C. A number of different approaches were trialled to visualise and measure the slagging propensity of bio-ash as a function of MgO content, as well as their comparison with reference coal ashes and several synthetic ashes generated by blending bio-ash with CaO, Al2 O3, SiO2 and K2 O individually and/or collectively. As has been found, the presence of 6–16 wt% MgO in bio-ash and coal ash exerted little influence on the ash fusion temperature. However, the slag flowability is slow for a relatively high viscosity of the bio-slags. In contrast, the coal slags flew much faster, although the formation of spinel crystals was confirmed in the high MgO content. Among the major basic oxides within bio-ash and coal ash, CaO is most influential in depolymerising ash matrix to promote its flowability. In contrast, the presence of Fe2 O3 is subtle, a small increase of whose content can cause the interaction with MgO for the formation of crystallised spinel. The co-presence of K2 O and Al2 O3 is the most negative, causing a significant decrease in the slag flowability. Finally, regarding the traditional methodologies for ash study, the base/acid (B/A) ratio for an overall balance between basic and acid oxides is unable to differentiate the discrepancy between coal ash and bio-ash. Likewise, the thermodynamic equilibrium prediction on liquidus amount and viscosity should be deemed as the empirical index that overlooks the kinetic control and formation of crystalline for the Mg-rich ash samples.